Reflection-in-action: Measuring ‘context’ in medical interpreting - Dean, Robyn (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Community interpreting scholarship has solidly established the importance of appreciating the nuances of context to effective interpreting practice (Angelelli, 2004; Wadensjo?, 1998). Several frameworks for identifying and articulating the way context affects interpreting work have been articulated (Dean & Pollard, 2011). What is less well documented is the way interpreters learn to develop an understanding of context and how that subsequently informs their practice. This article describes the development and implementation of a tool to assess interpreters’ facility in identifying and articulating context – specifically in healthcare settings. The activities and the assessment tool are grounded in the educational theories of Donald Schön and his foregrounding of the intuitive practice abilities of professionals. The resulting assessment tool was refined through its use in postgraduate courses in healthcare interpreting, where various aspects of the healthcare context were explained using videos of provider–patient interactions. Through reflective practice activities, students analysed their practical knowledge and skills and improved their context-based insight. Currently designed for signed language interpreters in medical settings based in the United States, this multi-component assessment tool can be adapted to various contexts in community interpreting.